2012
DOI: 10.1021/ie3006929
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling of Cobalt Based Catalyst Sintering in a Fixed Bed Reactor under Different Conditions of Fischer–Tropsch Synthesis

Abstract: A three-step sintering mechanism is proposed for Co-based catalysts under Fischer–Tropsch reaction conditions. This mechanism includes an intermediate formation of oxide layer on cobalt metal nanoparticles in the presence of water. The partially reversibly oxidized surface accelerates sintering by both reducing the surface energy and enhancing the diffusion rates of cobalt particles. The proposed mechanism is then employed for a fixed-bed unsteady state reactor. The effect of particle growth on the catalytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 46 publications
6
72
1
Order By: Relevance
“…Copper sintering seems to proceed according to particle migration and coalescence mechanism. Similar mechanism of nanoparticle sintering facilitated by the presence of water was previously observed for supported nickel and cobalt catalysts [42,43]. In addition to water, hydroxyl groups on the zeolite outer surface can obviously contribute to higher copper mobility in hybrid catalysts.…”
Section: Physicochemical Properties Of Catalysts Before and After Deasupporting
confidence: 69%
“…Copper sintering seems to proceed according to particle migration and coalescence mechanism. Similar mechanism of nanoparticle sintering facilitated by the presence of water was previously observed for supported nickel and cobalt catalysts [42,43]. In addition to water, hydroxyl groups on the zeolite outer surface can obviously contribute to higher copper mobility in hybrid catalysts.…”
Section: Physicochemical Properties Of Catalysts Before and After Deasupporting
confidence: 69%
“…Therefore, a particle migration and coalescence mechanism, as previously suggested by Sadeqzadeh et al [40] and Tsakoumis et al [41], is not observed on the model catalyst under the reaction conditions used. On supported catalysts, the mechanism of loss of metal surface area is typically derived from changes in the shape of the particle size distribution [40,41], while in the present study, changes are observed at the single-particle level (using TEM).…”
Section: Discussionmentioning
confidence: 71%
“…Primarily, X-ray absorption near edge (XANES) analysis shows simultaneous increasing extent of reduction and increasing Co-Co coordination, due both to removal of oxygen and increases in particle size. Second, water is believed to cause chemical-assisted sintering [80,367,[372][373][374], especially at high partial pressures that occur at CO conversions above about 65% [223], although the exact mechanisms are debated. Minor surface oxidation [373,374] and surface wetting [375] have been proposed, although Saib et al have shown that cobalt oxidation is not an important deactivation route [79] in catalysts with Co particles >~8 nm, which are typical in commercial FTS catalysts.…”
Section: Case Study: Cobalt Based Fischer-tropsch (Ft) Catalyst Regenmentioning
confidence: 99%